Measuring general mental health in early‐mid adolescence: A systematic meta‐review of content and psychometrics - Louise Black; Margarita Panayiotou; Neil Humphrey (Wiley, 2023)
Abstract Background Adolescent mental health is a major concern and brief general self‐report measures can facilitate insight into intervention response and epidemiology via large samples. However, measures' relative content and psychometrics are unclear. Method A systematic search of systematic reviews was conducted to identify relevant measures. We searched PsycINFO, MEDLINE, EMBASE, COSMIN, Web of Science, and Google Scholar. Theoretical domains were described, and item content was coded and analysed, including via the Jaccard index to determine measure similarity. Psychometric properties were extracted and rated using the COSMIN system. Results We identified 22 measures from 19 reviews, which considered general mental health (GMH) (positive and negative aspects together), life satisfaction, quality of life (mental health subscales only), symptoms, and wellbeing. Measures were often classified inconsistently within domains at the review level. Only 25 unique indicators were found and several indicators were found across the majority of measures and domains. Most measure pairs had low Jaccard indexes, but 6.06% of measure pairs had >50% similarity (most across two domains). Measures consistently tapped mostly emotional content but tended to show thematic heterogeneity (included more than one of emotional, cognitive, behavioural, physical and social themes). Psychometric quality was generally low. Conclusions Brief adolescent GMH measures have not been developed to sufficient standards, likely limiting robust inferences. Researchers and practitioners should attend carefully to specific items included, particularly when deploying multiple measures. Key considerations, more promising measures, and future directions are highlighted. PROSPERO registration: CRD42020184350 https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020184350.